A Proteção na Campanha Militar no Teatro de Operações de Angola (1961-1974) - Barradas, José (2018)
O presente trabalho destina-se a investigar o tema “A Proteção na Campanha Militar no Teatro de Operações de Angola (1961-1974) ”, contribuindo para um trabalho conjunto que se insere no título genérico “Análise da Campanha Militar no Teatro de Operações de Angola do ponto de vista das Forças Terrestres”. O percurso metodológico utilizado assentou em três fases: fase exploratória, consistindo em leituras preliminares de documentos, bibliografia diversa e entrevistas exploratórias; fase analítica, através da recolha de dados e a respetiva análise dos mesmos; fase conclusiva, onde foram elaboradas as conclusões e a redação do trabalho, tendo em vista a apresentação e defesa do mesmo. Verificámos que, no período em questão, não existia o conceito doutrinário de função de combate, nem a Proteção era abordada de forma independente. No entanto, as medidas de segurança previstas nos manuais doutrinários foram maioritariamente cumpridas e evoluindo com o decorrer da Campanha. Abstract: “Protection in the Military Campaign of Angola's Operation Theater (1961-1974)” aims to be part of a more comprehensive paper work which is entitled “Angola's Operation Theatre Military Campaign analysis from the Land Component point of vier”. The methodological approach used was based on three stages: exploratory stage, based on documents preliminary readings, miscellaneous bibliography and exploratory interviews; analytics stage, through data collection and analysis; conclusive stage, which comprises the writing of the paper and the conclusions, aim at the presentation and defense of paper. We concluded that in that period, the doutrinary concept of combat functions didn’t exist neither protection was independently approached. Nethertheless, safety measures existing in the doutrinary manuals were mostly undertaken and evolved through the Campaign. We concluded that in that period the combat function doutrinary concept didn’t exist and neither protection had an independent approach. Nevertheless, the security measures existing in the doutrinary manuals were being mostly fulfilled and also updated throughout the Campaing timeline.